The Differences in Historical Social Studies Learning Outcomes Between The Concept Map Learning Model and The Lecture Learning Model Vary - Fransiska, Lya (Universitas Negeri Semarang, 2016)
This article intends to examine differences in learning outcomes of IPS history subjects using a concept map of learning models compared with varied lecture models. Concept maps are applied in the experimental classes and lectures, and a varied learning model is applied in the control class. The population in this study consisted of students in grade IX SMP Negeri 1 Kandeman year 2011/2012, which amounted to 240 students. Sampling was conducted using random cluster sampling and obtained class A as class IX experiments (learning model concept map) and class class IX B as a control (lecture learning models vary). Learning outcomes by using a learning model map better than the concept of learning outcomes IPS History lecture on learning models vary. Advice and researchers hope that History Teachers can use the IPS model of learning a concept map as an alternative in teaching history to improve student learning outcomes and make learning history and social studies fun and exciting.